A Comparison of the present and preferred culture between the coaching staff and athletes of a collegiate sports team - Santos, Veronica G. 1997-; Gonzalo, Leilani G. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2019)
Organizational culture is one of the main factors that help in understanding how a group functions and is what distinguishes extraordinary successful organizations from others. The researcher applied the concepts of organizational culture (often in a corporate setting) in the context of an intercollegiate athletic varsity team. It has been seen to be common for intercollegiate athletic teams to have a cultural misalignment between their coaching staff and members. This study determined whether there is a misalignment between the perceived present and preferred cultures between the team's athletes and coaching staff. This empirical study used the Competing Values Framework (CVF) as its theoretical foundation, with The Organizational Culture Assessment Instrument (OCAI) to collect the necessary data. The OCAI consists of 6 domains which will help determine which type of organizational culture is perceived by each participant. The study's results showed that the collegiate team's present culture was misaligned with a margin of 15.52 points, where misalignment in culture would score a difference of more than 10 points (OCAI online, 2019). Despite this, the team showed close scores for all preferred culture types, which implied that both the athletes and coaching staff preferred the same culture types as compared to the present.
Vita.
Thesis (Bachelor in Sports Science)--University of the Philippines Diliman
Keywords: Coach-athlete relationships; Sports -- Psychological aspects